Hermeneutical characteristics of the notion of "Lebenswelt" in Edmund Husserl’s phenomenology - Furman, Marcin (Hybris, 2012)
The subject of this are the considerations concerning the “late” period of Edmund Husserl’s output and the notion of Lebenswelt. Husserl believes that any scientific knowledge, unlike analyses of common experience, requires new formal specification. Ipso facto cognitive absoluteness and its objectivity in a form of the “thing-in-itself” is moved to the background. A man cannot reach definitive cognition in this manner. Therefore cognition of life is the matter of principle.